Pre-Steady-State Kinetics of Catalytic Intermediates of an [FeFe]-Hydrogenase - Greene, Brandon L; Schut, Gerrit J; Adams, Michael W. W; Dyer, R. Brian (ACS catalysis, 2017)
[FeFe]-hydrogenases catalyze the reversible production of hydrogen gas from protons and electrons, but the mechanism of catalysis is still the subject of debate. In this report, we describe a pre-steady-state photoreduction methodology for correlating putative intermediates to the reactivity of an [FeFe]-hydrogenase from Thermotoga maritima. In this method, MV+ is rapidly formed photochemically by pulsed laser excitation and the intermolecular ET and active site dynamics are followed by nanosecond time-resolved visible and infrared spectroscopy, respectively. The results kinetically validate the Hox, Hred, and Hsred intermediates, strongly supporting a vast body of literature on their involvement in proton reduction.